Stability of high-entropy alloys under electrocatalytic conditions - Kormányos, Attila; Dong, Qi; Xiao, Bin; Li, Tangyuan; Savan, Alan; Jenewein, Ken; Priamushko, Tatiana; Körner, Andreas; Böhm, Thomas; Hutzler, Andreas; Hu, Liangbing; Ludwig, Alfred; et al. (iScience, 2023)
High-entropy alloys are claimed to possess superior stability due to thermodynamic contributions. However, this statement mostly lies on a hypothetical basis. In this study, we use on-line inductively coupled plasma mass spectrometer to investigate the dissolution of five representative electrocatalysts in acidic and alkaline media and a wide potential window targeting the most important applications. To address both model and applied systems, we synthesized thin films and carbon-supported nanoparticles ranging from an elemental (Pt) sample to binary (PtRu), ternary (PtRuIr), quaternary (PtRuIrRh), and quinary (PtRuIrRhPd) alloy samples. For certain metals in the high-entropy alloy under alkaline conditions, lower dissolution was observed. Still, the improvement was not striking and can be rather explained by the lowered concentration of elements in the multinary alloys instead of the synergistic effects of thermodynamics. We postulate that this is because of dissolution kinetic effects, which are always present under electrocatalytic conditions, overcompensating thermodynamic contributions.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Electrochemical materials science; Interfacial electrochemistry; Nanoelectrochemistry